Turning discarded blue shark (prionace glauca) skin into a valuable nutraceutical resource - Coscueta, Ezequiel R. (2024)
Marine-derived collagen, particularly from blue shark (Prionace glauca) skin, represents a sustainable resource for the nutraceutical industry, yet its effective utilisation remains underexplored. This study aims to optimise the enzymatic hydrolysis of blue shark skin collagen using alcalase and bromelain to enhance the bioactive properties of the resultant hydrolysates. We employed a multifactorial experimental design to determine the optimal hydrolysis conditions, assessing factors including enzyme concentration, pH, and temperature. The alcalase-treated hydrolysates demonstrated superior antioxidant and anti-inflammatory activities compared to those treated with bromelain, with increased solubilised proteins and a higher degree of hydrolysis. Notably, peptide profiles indicated that alcalase hydrolysates favoured the production of smaller peptides, suggesting enhanced bioavailability and digestive stability. In vitro gastrointestinal simulations demonstrated the functional stability of these peptides, indicating that while they undergo structural changes during digestion, their potential for gastrointestinal health remains significant. Our findings highlight the feasibility of converting blue shark skin, a commonly discarded by-product, into valuable nutraceutical ingredients, thus contributing to marine sustainability and waste reduction This research advances the biotechnological application of marine collagen and opens avenues for developing functional foods and pharmaceuticals.